Iodide-enhanced Cu-MOF nanomaterials for the amplified colorimetric detection of Fe3+. Issue 48 (30th November 2021) - Guan, Yan; Zhao, Xiao-Lan; Li, Qiu-Xia; Huang, Long; Yang, Jian-Mei; Yang, Tong; Yang, Yun-Hui; Hu, Rong
Abstract : In this paper, a novel colorimetric strategy based on iodide ion (I − ) and Cu-MOF catalysis was developed for simple, low-cost, and naked-eye detection of Fe 3+ . Abstract : In this paper, a novel colorimetric strategy based on iodide ion (I − ) and Cu-MOF catalysis was developed for simple, low-cost, and naked-eye detection of Fe 3+ . Both I − and MOFs display catalytic activity toward peroxidase substrate 3, 3′, 5, 5′-tetramethylbenzidine (TMB). Adsorption and embedding of I − in Cu-MOF generates Cu-MOF/I with a three-dimensional porous structure that exhibits higher specific surface area, providing more active sites to facilitate interaction with TMB, resulting in enhanced catalytic efficiency. Reports have shown that Fe 3+ can oxidize TMB in the absence of H2 O2 . We found that as Fe 3+ concentration increases, the color of the system gradually deepens and the UV absorption peak gradually increases, thus providing a colorimetric sensor for quantitative Fe 3+ detection. The detection limit (LOD) obtained in the presence of I − is 200 nM; however, in the absence of I −, the LOD is approx. 10 μM. Thus, the sensing system is ideal for signal amplified analysis of Fe 3+ . In the presence of various interfering metal ions, the developed sensing system displays excellent selectivity. Additionally, the practical application to Fe 3+ detection in real samples is explored.